Possibilities and Limitations of Dendrogeomorphic Time-Series Reconstructions on Sites Influenced by Debris Flows and Frequent Snow Avalanche Activity - Kogelnig-Mayer, Barbara; Stoffel, Markus; Schneuwly-Bollschweiler, Michelle; Hübl, Johannes; Rudolf-Miklau, Florian (Arctic, Antarctic, and Alpine Research, 2011)
Past debris-flow and snow avalanche activity was assessed for the Reiselehnrinne (Tyrol, Austria) using growth disturbances in growth-ring series of 372 Norway spruce (Picea abies (L.) Karst.) trees. Determination of events was performed by analyzing (a) the number and (b) intensity of growth disturbances within tree-ring series and (c) the spatial distribution of affected trees. Differentiation of debris flow from snow avalanche events was based on the intra-annual position of scars, callus tissues or tangential rows of traumatic resin ducts, and on the spatial distribution of trees with simultaneous reactions in the tree-ring series. We introduce a weighting factor to substantiate the dating of past process activity in a comprehensive way and to compare individual events as to their intensity and total number of tree-ring responses. The accuracy of the dendrogeomorphic assessment was then evaluated by comparing the reconstructed event frequency with chronologies available for the Reiselehnrinne. Comparison of tree-ring with historical data demonstrated clearly that the reconstructed event frequency contains the majority of past debris flow and snow avalanche events in the Reiselehnrinne, but that dating of events is not always possible, especially if they are clustered in time or have a limited spread on the cone.